Pengaruh Model Problem-Based Learning Berbantuan LKPD Multirepresentasi Terhadap Keterampilan Argumentasi Ilmiah Siswa SMP Pada Pembelajaran IPA - Rina Jayati; Supeno Supeno; Lilik Budiani (Universitas Garut, 2026)
This study aims to explore the level of students' scientific argumentation skills before and after learning with the PBL model accompanied by a multirepresentation worksheet, as well as examining the effect of the application of the model on the scientific argumentation skills of junior high school students in science learning. The approach in this research is quantitative using a quasi-experimental type in the form of nonequivalent control group design. Data were collected via test and non-test techniques; test instruments are scientific arguments, while non-test instruments include interviews, observations, and documentation. The results showed that students' scientific argumentation skills before learning were in the weak category, and increased to a strong category after implementation of the PBL model assisted by multirepresentation worksheets. The results of an independent sample t-test produces a sig value. (2-tailed) which is 0.000 < 0.05, which proves that the application of the model to scientific argumentation skills has a significant influence. Therefore, the conclusion is that the multirepresentation worksheet-assisted PBL model significantly affects the scientific argumentation skills for junior high school students in science learning, from the weak category to the strong category.Keywords: Multirepresentation worksheet, problem-based learning, science learning, scientific argumentation